STATUS GIZI KURUS ANAK USIA (24-59) BULAN DENGAN DI NANGGROE ACEH DARUSSALAM Analisis Data Surkesda NAD 2006 - Muljati, Sri; ., Sandjaja (PERSATUAN AHLI GIZI INDONESIA, 2008)
THE PREVALENCE OF WASTINGOF CHILDREN AGE 24-59 MONTHS IN NANGGROE ACEH DARUSSALAMSurkesda NAD 2006 as post tsunami household health survey and covering all 21 districts/citieshad assessed child nutritional status (wasting), with cut-off point <-2.00 SD for age 24-59 months.A total sample of 922 children was included in the assessment. The objective of this study is toanalyze child nutritional status and factors related to the status in NAD after tsunami. The studyrevealed that the prevalence of wasting in NAD was 16.7% (ranges from 5.9%-31.3%). Theprevalence of wastingin NAD were higher than those of Indonesia. Multivariate analysis identifiedvarious factors that associated with the prevalence of wasting. Higher risk of wasting wasidentified for children (24-59 months) with absence of BCG immunization (OR=1.63), and thoseattending out-patient clinics for treatment of their illnesses (OR=1.47). It is recommended thatintensive nutrition program be implemented in high areas of wasting through exclusive breastfeeding promotion, proper complementary food distribution, growth monitoring and promotion, IECfor nutrition and child caring practices.Keywords: child nutritional status, tsunami, Aceh, balita